2017
DOI: 10.3892/ol.2017.7500
|View full text |Cite
|
Sign up to set email alerts
|

Down‑expression of poly(ADP‑ribose) polymerase in p53‑regulated pancreatic cancer cells

Abstract: Abstract. The present study investigated whether poly(ADP-ribose) polymerase (PARP) has an effect on p53-regulated pancreatic cancer. The results of the present study demonstrated that the expression of PARP affects proliferation and apoptosis of pancreatic cancer cells. Olaparib was used to suppress the expression level of PARP-1 in PanC-1 cells. Decreased expression of PARP-1 suppressed cell proliferation and induced apoptosis of PanC-1 cells when compared with controls. Furthermore, decreased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…However, we observed a significant downregulation of the expression of total PARP-1 in MCF-7 and MDA-MB-453 cells. PARP-1 is overexpressed in different types of cancer, including prostate, pancreatic, and breast, and it has been reported that decreased expression of PARP-1 inhibited cell proliferation and induced apoptosis in pancreatic cancer cells [ 62 ]. In addition, the degradation of PARP-1 mediated by caspase-independent ubiquitylation which has a role in apoptosis, necrosis, and other cellular processes has been reported [ 63 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed a significant downregulation of the expression of total PARP-1 in MCF-7 and MDA-MB-453 cells. PARP-1 is overexpressed in different types of cancer, including prostate, pancreatic, and breast, and it has been reported that decreased expression of PARP-1 inhibited cell proliferation and induced apoptosis in pancreatic cancer cells [ 62 ]. In addition, the degradation of PARP-1 mediated by caspase-independent ubiquitylation which has a role in apoptosis, necrosis, and other cellular processes has been reported [ 63 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis analysis results of the present study have shown an increased apoptosis of pancreatic cells after treatment with 40µM of olaparib, and these differences were found to be statistically signi cant for BRCA KD cells (P < 0.01). In fact olaparib is known to induce apoptosis of cancer cells (44,45). In this respect, our in vitro results suggest that BRCA KD cells may have clinically relevant response to olaparib treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Poly (ADP ribose) polymerase (PARP) is a DNA repair protein that helps cancer cells to reduce stress. 46,47 Downregulation of PARP protein (Fig. 11A and C) was observed with CCS treatment, suggesting irreversible DNA repair and enhanced stress.…”
Section: Resultsmentioning
confidence: 97%